Spectrum of surgical site infection on the surgical floor; Increasing resistance to routine antibiotics - Muhammad Iqbal, Naveed Akhtar Malik, Muhammad Hanif (Journal of Rawalpindi Medical College, 2021)
Objective: To know the spectrum of surgical site infections in general surgical patients so that specific strategies can be developed to decrease the morbidity caused by these infections. Material and Methods: All the patients who underwent general surgical operations on an emergency basis at the surgical unit of the District headquarters teaching hospital Rawalpindi from 01-01-2016 to 31-12-2017 were evaluated for surgical site infections. Surgical site infections suspected clinically were confirmed by culture and sensitivity. Involved flora and their sensitivity to various antibiotics were also determined. Results: Among 2202 emergency operated patients, two hundred and thirty-seven patients (10.76%) had surgical site infection confirmed on culture and sensitivity (C/S) report. About sixty-five percent of patients were male. Of two hundred and thirty-seven positive patients, the twenty-nine patient underwent laparotomy for penetrating and blunt abdominal trauma. Staph aureus was present in one hundred and forty-five (79.67%) patients. E.coli was the commonest Gram-ve micro-organism (70.95%). Forty-six patients (19.40%) were sensitive to Cefoperazone sodium followed by twenty patients (8.43%) to Piperacillin sodium and twenty-one (8.86%) each to Amikacin and Linezolid. Conclusion: Surgical site infection causes a significant rise in morbidity on the surgical floor. Most of the causative microorganisms are becoming resistant to routine antibiotics. Sensitivity to the broader spectrum of antibiotics like Cefoperazone and Linezolid is increasing.